Ontological Study of The Classification of People in The Transfer of Land Rights in Realizing Legal Certainty - Rahadi Wasi Bintoro; Antonius Sidik Maryono; Sanyoto Sanyoto; Weda Kupita; Noor Dzuhaidah Osman (UNNES Fakultas Hukum, 2024)
Non-Indexed Publication